Structure and reversibility of 2D hexagonal cellular automata - Siap, Irfan; Akin, Hasan; Uguz, Selman (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Cellular automata are used to model dynamical phenomena by focusing on their local behavior which depends on the neighboring cells in order to express their global behavior. The geometrical structure of the models suggests the algebraic structure of cellular automata. After modeling the dynamical phenomena, it is sometimes an important problem to be able to move backwards in order to understand it better. This is only possible if cellular automata is reversible. In this paper, 2D finite cellular automata defined by local rules based on hexagonal cell structure are studied. Rule matrix of the hexagonal Finite cellular automaton is obtained. The rank of rule matrices representing the 20 hexagonal finite cellular automata via an algorithm is computed. It is a well known fact that determining the reversibility of a 2D cellular automata is a very difficult problem in general. Here, the reversibility problem of this family of 2D hexagonal cellular automata is also resolved completely. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Hexagonal cellular automata; Rule matrix; Reversible cellular automata; Matrix algebra; CRYPTOGRAPHY; RULES; Mathematics